OPEN ACCESS TO KNOWLEDGE AND LIBRARIES: ACHIEVEMENTS AND TRENDS - O’Donnell, Loretta (Nazarbayev University library, 2022)
This is a welcoming presentation which covers following aspects: Open Access to Knowledge, Leverage curiosity, Leverage intellectual capital, Leverage integrity
Keywords: Type of access: Open Access; Open Access; Academic Integrity